Development of practical HPLC methods for the separation and determination of eggplant steroidal glycoalkaloids and their aglycones - Eanes, Ritchie C.; Tek, Neslihan; Kirsoy, Oykum; Frary, Anne; Doganlar, Sami; Almeida, Adelia E. [UNESP] (Taylor & Francis Inc, 2008)
A practical set of HPLC methods was developed for the separation and determination of the eggplant steroidal glycoalkaloids, solanine, chaconine, solasonine, solamargine, and their aglycones, solasodine and solanidine. A gradient method was initially developed, but proved to be neither robust nor practical. Three separate isocratic methods using acetonitrile and ammonium dihydrogen phosphate were developed and shown to be more repeatable, less subject to fluctuations in mobile phase composition, and less time consuming. The effect of adjusting buffer pH, column temperature, and buffer type (triethylammonium phosphate vs. ammonium dihydrogen phosphate) were evaluated. It was also discovered that, by addition of 10% methanol to the acetonitrile portion of the mobile phase, more control over the separations was possible. The use of methanol as a mobile phase entrainer greatly improved separations in some cases and its effectiveness was also dependent upon column temperature. Assessments of the method recovery, limit of detection, and limit of quantitation were made using extracts from S. melongena and S. linnaeanum.
Keywords: HPLC; eggplant; solanine; chaconine; solamargine; solasonine; solanidine; solasodine; steroidal glycoalkaloids